2017
DOI: 10.1186/s12872-017-0651-x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic function changes in hypertrophic cardiomyopathy patients detected by the strain of different myocardium layers and longitudinal rotation

Abstract: Background: Impairment of left ventricular (LV) longitudinal function has an important role in hypertrophic cardiomyopathy (HCM). This research investigated an association between the longitudinal strain of different myocardial layers, longitudinal rotation and the LV systolic function of HCM patients. Methods: The research was performed on 36 HCM patients and 36 healthy subjects. The peak systolic longitudinal strain of the subendocardial, midmyocardial, and subepicardial layers was measured using 2-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…RA functions play an important role in the cardiac and 2D-STE is a feasible, angle-independent method for the evaluation of RA function [ 24 ]. Researchers mainly focused RA functions on pulmonary artery hypertension, acute pulmonary embolism, hypertension, the influence of severity tricuspid regurgitation, right ventricular myocardial infarction, tetralogy of Fallot, and so on [ 11 , 12 , 25 27 ]. However, till now, we have not found a research about RA functions in HCM patients by using 2D-STE and RA volume-derived values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA functions play an important role in the cardiac and 2D-STE is a feasible, angle-independent method for the evaluation of RA function [ 24 ]. Researchers mainly focused RA functions on pulmonary artery hypertension, acute pulmonary embolism, hypertension, the influence of severity tricuspid regurgitation, right ventricular myocardial infarction, tetralogy of Fallot, and so on [ 11 , 12 , 25 27 ]. However, till now, we have not found a research about RA functions in HCM patients by using 2D-STE and RA volume-derived values.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two-dimensional speckle tracking echocardiography (2D-STE) for detecting the strain and strain rate in RA functions were mainly focused on patients with pulmonary artery hypertension, acute pulmonary embolism and tricuspid regurgitation severity [ 11 13 ]. These studies were necessary to demonstrate that the technique could detect the RA functions flexibility and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The layerspecific speckle tracking (LST) technology, derived from 2D-STE, can analyze strain parameters of LV function in three muscular layersthe sub-endocardium, midmyocardium, and sub-epicardium [11]. Therefore, LST allows early detection of subtle ventricular systolic dysfunction [11][12][13]. Previous studies used the LST to assess global longitudinal, circumferential, and radial myocardial strains of dialysis patients [14][15][16], but few studies have been performed to measure longitudinal and circumferential strains of the LV three-layer myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…When the longitudinal and circumferential myocardium contract and relax, the cardiac myocardium deformation occurs in three directions: longitudinally, circumferentially, and radially. Our previous study showed that in HCM patients, the longitudinal function was damaged, even with normal LV ejection fraction [ 19 ], however, short-axis cardiac function as circumferentially and radially is also essential like longitudinally function. So, in this study, we mainly analysed the short-axis function in HCM patients.…”
Section: Introductionmentioning
confidence: 99%